Method for inhibiting shuttling of polyiodide in zinc-iodine battery

By coating the polysaccharide gel protective film on the cathode material surface of the zinc-iodine battery, the problem of multiple iodide shuttle in zinc-iodine battery is solved, and the stability of battery performance and the service life are extended.

CN119905688APending Publication Date: 2025-04-29JINZHONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510110674.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

During the repeated charging and discharging of zinc-iodine batteries, the shuttle of multiple iodides leads to a decline in battery performance or even scrapping, and the prior art is difficult to effectively suppress this problem.

Method used

A transparent gel is prepared by physical or chemical cross-linking method using polysaccharide gel and coated on the surface of the cathode material adsorbed with iodine substances to form a protective film to inhibit the shuttle of polyiodide.

Benefits of technology

It achieves effective restrictions on the multiple iodides in zinc-iodine batteries, extends the service life of the battery, avoids performance degradation and battery scrapping, and is low in cost and simple in operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905688A_ABST
    Figure CN119905688A_ABST
Patent Text Reader

Abstract

The invention discloses a method for inhibiting shuttling of polyiodide in a zinc-iodine battery, and belongs to the technical field of polysaccharide gel and zinc-iodine batteries. Aiming at the problem of shuttling of polyiodide in the existing zinc-iodine battery, transparent polysaccharide gel is prepared from a polysaccharide substance by a physical crosslinking method or a chemical crosslinking method; loading the cathode material adsorbed with the iodine substance on a conductive substrate, and coating the outer layer with the polysaccharide gel to obtain a polysaccharide gel protective film modified cathode; and assembling the zinc anode, the polysaccharide gel protective film modified cathode and the electrolyte into the zinc-iodine battery without multi-iodide shuttling. According to the invention, the gel is prepared from a polysaccharide substance and is coated on the surface of the cathode of the zinc-iodine battery, and through chemical and physical adsorption of the polysaccharide gel on the polyiodide, the purpose of inhibiting shuttling of the polyiodide can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polysaccharide gel and zinc-iodine battery, and particularly relates to a method for inhibiting the shuttling of polyiodides in zinc-iodine batteries. Background Art

[0002] Zinc-iodine batteries have the advantages of high specific capacity and low cost, and have attracted widespread attention. However, during the repeated charge and discharge process of zinc-iodine batteries, the shuttling of polyiodides causes the performance of zinc-iodine batteries to decline and even leads to battery scrapping, which seriously hinders the development of zinc-iodine batteries. It is urgent to develop a zinc-iodine battery without polyiodide shuttling. Generally, (1) by using nanoporous materials, graphene, etc. to fix iodine in the cathode material through physical adsorption or chemical bonding, some polyiodides can be bound; (2) by using ion-selective materials or molecular sieves as battery separators to prevent the shuttling of polyiodides; (3) by using high-concentration electrolytes or solid electrolytes to inhibit the free I - The free movement of iodide can be inhibited, thereby achieving the purpose of inhibiting the shuttling of multiple iodides. (Adv. Mater., 2022, 34, 2108856; Energy Storage Mater., 2021, 35, 687; Adv. Mater., 2020, 32, 1905361; Chem. Eng. J., 2021, 21, 4129; Energy Environ. Sci., 2021, 14, 407; Energy Environ. Sci., 2021, 14, 3492; Angew. Chem. Int. Ed., 2019, 58, 15910; ACS Nano, 2022, 16, 13554) However, in the above method, porous materials and other materials have limited fixation of iodine, and long-term charge and discharge cycles will still produce polyiodides; the ion-selective diaphragm or molecular sieve has a tortuous path, which will cause low ion conductivity while inhibiting the shuttle of polyiodides; the problems of poor kinetic performance and high preparation cost caused by high concentration or solid electrolytes still need to be further improved. Therefore, it is of great significance to develop a preparation technology for zinc-iodine batteries that is low in cost, easy to operate, and can effectively inhibit the shuttle of polyiodides. Summary of the invention

[0003] In view of the problem of multi-iodide shuttling in current zinc-iodine batteries, the present invention provides a method for inhibiting multi-iodide shuttling in zinc-iodine batteries with simple process, low cost and strong universality.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] A method for inhibiting multi-iodide shuttling in a zinc-iodine battery comprises the following steps:

[0006] Step 1, preparing a transparent polysaccharide gel by physical or chemical cross-linking of the polysaccharide material;

[0007] Step 2, loading the cathode material adsorbed with iodine substance on a conductive substrate, and coating the outer layer with polysaccharide gel to obtain a polysaccharide gel protective film modified cathode;

[0008] Step 3, assemble the zinc anode, the polysaccharide gel protective film modified cathode and the electrolyte into a zinc-iodine battery without poly-iodide shuttle.

[0009] Furthermore, the polysaccharide material in step 1 is any one or more of starch, chitosan, guar gum, cellulose or hyaluronic acid.

[0010] Furthermore, the physical cross-linking method is to dissolve the polysaccharide substance in water, continuously stir and heat to obtain a transparent sol, and then cool it at room temperature.

[0011] Furthermore, the chemical cross-linking method is to dissolve the polysaccharide substance in water, and then continuously stir and heat to obtain a transparent sol, add a cross-linking agent thereto, stir evenly, and then cool at room temperature;

[0012] Furthermore, the cross-linking agent is any one of glutaraldehyde, boric acid and epichlorohydrin.

[0013] Furthermore, the concentration of the polysaccharide gel is 10 to 80 mg / mL.

[0014] Furthermore, the heating temperature of the physical and chemical cross-linking method in step 1 is 70-100°C.

[0015] Furthermore, the cathode material adsorbed with iodine in step 2 is any one of activated carbon, graphene, carbon nanotubes, polypyrrole, and polyaniline.

[0016] Furthermore, in step 2, the conductive substrate is any one of carbon cloth, carbon fiber, carbon felt, titanium sheet, and stainless steel sheet.

[0017] Further, in step 3, the electrolyte is any one of zinc sulfate, zinc chloride, zinc nitrate, zinc gluconate, zinc sulfate and potassium iodide, zinc sulfate and zinc iodide, zinc chloride and potassium iodide, zinc chloride and zinc iodide, zinc nitrate and potassium iodide, zinc nitrate and zinc iodide, zinc gluconate and potassium iodide, and zinc gluconate and zinc iodide.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] 1. The polysaccharide gel of the present invention has low cost and simple preparation method. The functional groups such as hydroxyl groups in the polysaccharide can effectively restrict polyiodide, thereby achieving the purpose of restricting the shuttling of polyiodide.

[0020] 2. In the present invention, the polysaccharide gel is coated on the surface of the cathode material that can be used for zinc-iodine batteries, and the polyiodide is confined in the cathode material. This method is simple to operate and has strong universality, and can be used on any zinc-iodine battery cathode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The zinc-iodine battery prepared in Example 1 of the present invention was scanned at a rate of 0.2 mV s -1 Cyclic voltammetry curves.

[0022] Figure 2 This is a schematic diagram of the voltage retention rate of the zinc-iodine battery prepared in Example 1 of the present invention after being fully charged at a current density of 0.2 A / g and left to stand for 24 hours.

[0023] Figure 3 The zinc-iodine battery prepared in Example 1 of the present invention was fully charged at a current density of 0.2 A / g and then allowed to stand for 24 hours and then charged at a current density of 0.2 A / g. -1 Self-discharge test diagram of current density discharge.

[0024] Figure 4 This is a test diagram of the rate performance and coulombic efficiency of the zinc-iodine battery prepared in Example 2 of the present invention.

[0025] Figure 5 This is a schematic diagram of the flexible zinc-iodine battery prepared in Example 3 of the present invention undergoing 3000 cycle stability tests.

[0026] Figure 6 This is a UV-visible spectrum of the electrolyte in the zinc-iodine battery prepared in Example 4 of the present invention during the charging process. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] A method for inhibiting multi-iodide shuttling in a zinc-iodine battery comprises the following steps:

[0030] 1) Add 500 mg of starch to 10 mL of deionized water, stir at 80 °C until the gel becomes colorless and transparent, and cool at room temperature to obtain a concentration of 50 mg mL -1 of starch gel.

[0031] 2) Place the porous carbon in 1 mol L -1 KI and 70 mg mL -1 The mixture was fully reacted in a mixed solution of I2 for 24 hours, and the porous carbon material adsorbed with iodine was obtained after filtration, washing and drying. The porous carbon material with iodine, acetylene black and hydroxymethyl cellulose were evenly ground in a ratio of 8:1:1 and evenly coated on a carbon cloth. The starch gel was evenly coated on the surface of the above materials and dried at room temperature to obtain a cathode material modified with starch gel.

[0032] 3) Prepare 10 mL of a mixed solution of 2 mol / L zinc sulfate and 0.05 mol / L potassium iodide as an electrolyte.

[0033] 4) The zinc anode, starch gel-modified cathode material and electrolyte are assembled into a zinc-iodine battery without poly-iodide shuttling.

[0034] Figure 1 The zinc-iodine battery prepared in Example 1 of the present invention was scanned at a rate of 0.2 mV s -1 Cyclic voltammetry curve. It can be seen from the figure that the cyclic voltammetry curve of the device shows an obvious redox peak.

[0035] Figure 2 The zinc-iodine battery prepared in Example 1 of the present invention can maintain a voltage of 83.3% after being fully charged at a current density of 0.2 A / g and left to stand for 24 hours.

[0036] Figure 3 The zinc-iodine battery prepared in Example 1 of the present invention was fully charged at a current density of 0.2 A / g and then allowed to stand for 24 hours. -1 Self-discharge test diagram of current density discharge. After 24 hours of standing, the battery capacity can reach 86.8% of the unstanding capacity, showing good self-discharge suppression performance.

[0037] Example 2

[0038] A method for inhibiting multi-iodide shuttling in a zinc-iodine battery comprises the following steps:

[0039] 1) Add 600 mg chitosan to 10 mL 2% phosphoric acid aqueous solution and stir at room temperature until the gel becomes transparent to obtain a concentration of 60 mg mL -1 of chitosan gel.

[0040] 2) placing the porous carbon and the iodine element in a sealed glass bottle and heating them at 90° C. for 24 hours, washing them with ethanol until the supernatant is colorless and transparent, filtering, washing, and drying to obtain a porous carbon material adsorbed with iodine, grinding the porous carbon material with iodine, acetylene black, and hydroxymethyl cellulose in a ratio of 8:1:1 and evenly coating them on a carbon cloth, evenly coating the starch gel on the surface of the above materials, and drying them at room temperature to obtain a cathode material modified with starch gel.

[0041] 3) Prepare 10 mL of 2 mol L -1 of zinc sulfate and 0.05 mol L -1 A mixed solution of potassium iodide was used as the electrolyte.

[0042] 4) The zinc anode, chitosan gel-modified cathode material and electrolyte are assembled into a zinc-iodine battery without poly-iodide shuttling.

[0043] Figure 4 The rate performance and coulombic efficiency of the zinc-iodine battery prepared in Example 2 of the present invention were tested, wherein the current density was 0.2 mA g -1 , the specific capacity is 269.4 mAh g -1 , the Coulomb efficiency is 90.7%, showing good capacitive performance.

[0044] Example 3

[0045] A method for inhibiting multi-iodide shuttling in a zinc-iodine battery comprises the following steps:

[0046] 1) Add 400 mg of starch to 10 mL of deionized water and stir at 80 °C until the gel is colorless and transparent. Add 2 mL of 5% glutaraldehyde dropwise and stir evenly. Cool at room temperature to obtain a gel with a concentration of 40 mg mL -1 Chemically cross-linked starch gel.

[0047] 2) Place the porous carbon in 1 mol L -1 KI and 70 mg mL -1 The mixture was fully reacted in a mixed solution of I2 for 24 hours, and the porous carbon material adsorbed with iodine was obtained after filtration, washing and drying. The porous carbon material with iodine, acetylene black and hydroxymethyl cellulose were evenly ground in a ratio of 8:1:1 and evenly coated on a carbon cloth. The starch gel was evenly coated on the surface of the above materials and dried at room temperature to obtain a cathode material modified with starch gel.

[0048] 3) Prepare 10 mL of 2 mol L -1 of zinc sulfate and 0.05 mol L -1 The mixed solution of potassium iodide was uniformly mixed with 1 mg of hydroxymethyl cellulose and stirred at 80°C until the gel was colorless and transparent to obtain a solid gel electrolyte.

[0049] 4) The zinc anode, starch gel-modified cathode material and solid gel electrolyte are assembled into a flexible zinc-iodine battery without poly-iodide shuttling.

[0050] Figure 5 The capacity of the flexible zinc-iodine battery prepared in Example 3 of the present invention can reach 94.4% of the initial capacity after 3000 cycle stability tests, showing good stability.

[0051] Example 4

[0052] A method for inhibiting multi-iodide shuttling in a zinc-iodine battery comprises the following steps:

[0053] 1) Add 600 mg of starch to 10 mL of deionized water, stir at 80 °C until the gel becomes colorless and transparent, and cool at room temperature to obtain a concentration of 60 mg mL -1 of starch gel.

[0054] 2) placing polypyrrole and iodine in a sealed glass bottle and heating at 90° C. for 24 hours, washing with ethanol until the supernatant is colorless and transparent, filtering, washing, and drying to obtain polypyrrole adsorbed with iodine, grinding the polypyrrole with iodine, acetylene black, and hydroxymethyl cellulose in a ratio of 8:1:1 and evenly coating them on carbon cloth, evenly coating starch gel on the surface of the above materials, and drying at room temperature to obtain a cathode material modified with starch gel.

[0055] 3) Prepare 10 mL of 1 mol L -1 of zinc sulfate and 0.05 mol L -1 A mixed solution of zinc iodide was used as the electrolyte.

[0056] 4) The zinc anode, starch gel-modified cathode material and electrolyte are assembled into a zinc-iodine battery without poly-iodide shuttling.

[0057] Figure 6 This is a UV-visible spectrum of the electrolyte in the zinc-iodine battery prepared in Example 4 of the present invention during the charging process. The characteristic peaks of polyiodides do not increase significantly during the charging process, showing good performance in inhibiting polyiodide shuttling.

[0058] The contents not described in detail in the specification of the present invention belong to the prior art known to the professional and technical personnel in the field. Although the illustrative specific embodiments of the present invention are described above to facilitate the understanding of the present invention by the technical personnel in the field, it should be clear that the present invention is not limited to the scope of the specific embodiments. For the ordinary technical personnel in the field, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.

Claims

1. A method for inhibiting polyiodide shuttling in a zinc-iodine battery, characterized in that: The following steps are involved: Step 1, preparing a transparent polysaccharide gel by physical or chemical cross-linking of the polysaccharide material; Step 2, loading the cathode material adsorbed with iodine substance on a conductive substrate, and coating the outer layer with polysaccharide gel to obtain a polysaccharide gel protective film modified cathode; Step 3, assemble the zinc anode, the polysaccharide gel protective film modified cathode and the electrolyte into a zinc-iodine battery without poly-iodide shuttle.

2. A method for inhibiting polyiodide shuttling in a zinc-iodine battery according to claim 1, characterized in that: The polysaccharide material in step 1 is any one or more of starch, chitosan, guar gum, cellulose or hyaluronic acid.

3. A method for inhibiting polyiodide shuttling in a zinc-iodine battery according to claim 1, characterized in that: The physical cross-linking method is to dissolve the polysaccharide substance in water, continuously stir and heat to obtain a transparent sol, and then cool it at room temperature.

4. A method for inhibiting polyiodide shuttling in a zinc-iodine battery according to claim 1, characterized in that: The chemical cross-linking method is to dissolve the polysaccharide substance in water, and then continuously stir and heat to obtain a transparent sol, add a cross-linking agent into the sol, stir evenly, and then cool at room temperature.

5. A method for inhibiting polyiodide shuttling in a zinc-iodine battery according to claim 4, characterized in that: The cross-linking agent is any one of glutaraldehyde, boric acid and epichlorohydrin.

6. A method for inhibiting polyiodide shuttling in a zinc-iodine battery according to claim 1, characterized in that: The concentration of the polysaccharide gel is 10-80 mg / mL.

7. A method for inhibiting polyiodide shuttling in a zinc-iodine battery according to claim 1, characterized in that: In the step 1, the heating temperature for preparing the transparent polysaccharide gel by the physical cross-linking method or the chemical cross-linking method is 70° C. to 100° C.

8. A method for inhibiting polyiodide shuttling in a zinc-iodine battery according to claim 1, characterized in that: The cathode material adsorbed with iodine in step 2 is any one of activated carbon, graphene, carbon nanotubes, polypyrrole, and polyaniline.

9. A method for inhibiting polyiodide shuttling in a zinc-iodine battery according to claim 1, characterized in that: In step 2, the conductive substrate is any one of carbon cloth, carbon fiber, carbon felt, titanium sheet, and stainless steel sheet.

10. The method for inhibiting multi-iodide shuttling in a zinc-iodine battery according to claim 1, characterized in that: In step 3, the electrolyte is any one of zinc sulfate, zinc chloride, zinc nitrate, zinc gluconate, zinc sulfate and potassium iodide, zinc sulfate and zinc iodide, zinc chloride and potassium iodide, zinc chloride and zinc iodide, zinc nitrate and potassium iodide, zinc nitrate and zinc iodide, zinc gluconate and potassium iodide, and zinc gluconate and zinc iodide.